Immunogenicity of the Adjuvanted Recombinant Zoster Vaccine: Persistence and Anamnestic Response to Additional Doses Administered 10 Years After Primary Vaccination - Hastie, Andrew; Catteau, Grégory; Enemuo, Adaora; Mrkvan, Tomas; Salaun, Bruno; Volpe, Stephanie; Smetana, Jan; Rombo, Lars; Schwarz, Tino; Pauksens, Karlis; Hervé, Caroline; Bastidas, Adriana; et al. (The Journal of infectious diseases, 2021)
BACKGROUND: The adjuvanted recombinant zoster vaccine (RZV) is highly immunogenic and efficacious in adults ≥50 years of age. We evaluated (1) long-term immunogenicity of an initial 2-dose RZV schedule, by following up adults vaccinated at ≥60 years of age and by modeling, and (2) immunogenicity of 2 additional doses administered 10 years after initial vaccination. METHODS: Persistence of humoral and cell-mediated immune (CMI) responses to 2 initial RZV doses was assessed through 10 years after initial vaccination, and modeled through 20 years using a Piecewise, Power law and Fraser model. The immunogenicity and safety of 2 additional RZV doses were also evaluated. RESULTS: Seventy adults were enrolled. Ten years after initial vaccination, humoral and CMI responses were approximately 6-fold and 3.5-fold, respectively, above those before the initial vaccination levels. Predicted immune persistence through 20 years after initial vaccination was similar across the 3 models. Sixty-two participants (mean age [standard deviation], 82.6 [4.4] years) received ≥1 additional RZV dose. Strong anamnestic humoral and CMI responses were elicited by 1 additional dose, without further increases after a second additional dose. CONCLUSIONS: Immune responses to an initial 2-dose RZV course persisted for many years in older adults. Strong anamnestic immune responses can be induced by additional dosing 10 years after the initial 2-dose course. CLINICAL TRIALS REGISTRATION: NCT02735915.
Keywords: safety; syntetické vakcíny; herpes zoster; adjuvanted recombinant zoster vaccine; Adjuvants, Immunologic; vakcinace; Herpes Zoster Vaccine; lidé; virus varicella zoster; Herpes Zoster; Herpesvirus 3, Human; Aged, 80 and over; Vaccines, Synthetic; Vaccination; Aged; persistence of immune response; Immunogenicity, Vaccine; lidé středního věku; senioři nad 80 let; senioři; imunogenicita vakcíny; adjuvancia imunologická; Middle Aged; vakcína proti pásovému oparu; Humans